Nephrectomy or nephron-sparing surgery – how to decide? - Łuczyńska, Elżbieta; Dyczek, Sonia; Heinze-Paluchowska, Sylwia; Komorowski, Artur; Pawlik, Tomasz; Wysocki, Wojciech; Klimek, Małgorzata (Contemporary Oncology/Współczesna Onkologia, 2013)
Aim of the study : Radical nephrectomy in the treatment of renal cell carcinoma (RCC) remains the gold standard, but nephron-sparing surgery (NSS) is still increasing in importance. The main goal of this study was to compare the diagnostic accuracy of ultrasound and multi-detector computed tomography in RCC staging and its influence on deciding about further patient treatment. Material and methods : 87 patients (age range 27–90 years; median 61.5) underwent ultrasound (US) scan and contrast-enhanced computed tomography (CE-CT) of the abdomen and pelvis. 28 patients were qualified for NSS. The remaining group of patients underwent nephrectomy. Results : NSS was performed more frequently among patients with lesions in the lower pole of the kidney and there was no infiltration to the calyx and renal pelvis. Radical nephrectomy (RN) was pursued in cases with lesions in the central or upper pole. Lesion diameter in patients qualified for NSS was smaller than in patients qualified for radical nephrectomy. Conclusions : Determining the relationship between tumour and adjacent structures is not a simple matter. According to our study, 50% of CT results differ from histopathology assessment. Tumour diameter determined in CT examination is larger than in ultrasound and histopathological measurements while US scanning tends to underestimate tumour size in relation to histopathological assessment.